Comparison of Pancasila Education Learning Using Chat GPT and Google on Learning Outcomes - Pratama, Marchel Septi; Akhwani, Akhwani; Rulyansah, Afib; Susanto, Rudi Umar (BASICA Journal of Arts and Science in Primary Education, 2024)
This research aims to compare the effects of using Chat GPT and Google on student learning outcomes in Pancasila Education at UPT SD Negeri 158 Gresik. The study employed a Pretest-Posttest design, involving a total of 64 students who were divided into two groups. Data were collected through student assessment worksheets comprising multiple-choice and essay questions. The data were analyzed using the non-parametric Mann-Whitney U test to compare the learning outcomes between the two groups. The results indicated that both groups, those using Chat GPT and those using Google, showed a significant improvement in learning outcomes from Pretest to Posttest. The average score for the Chat GPT group was 92.74, while the Google group scored an average of 92.30, with a marginal difference of 0.44. However, there was no significant difference in student learning outcomes between the two groups at the Posttest stage. This is supported by a significance value of 0.708 from the Mann-Whitney U test, which is greater than 0.05, indicating no statistically significant difference between the groups' average Posttest scores. This research contributes to understanding the role of technology in Pancasila Education. The practical implications underscore the importance of integrating technology into the learning process. Although both technologies positively impact learning outcomes, there is no significant difference between Chat GPT and Google in the context of Pancasila Education at UPT SD Negeri 158 Gresik.